Strategic Financial Management: Exercices - Hill, Alan (R.A.Hill & Ventus Publishing, 2012)
This book of exercises and solutions tests your knowledge of Strategic Financial Management. It also develops a number of theoretical concepts outlined in the companion text as a guide to further study.